Mobilisasi Dini dan Proses Penyembuhan Luka Post Operasi Abdominal Pada Fase Inflamasi - Daiyana, Intan; Hermansyah, Hermansyah; Raharjo, Setio Budi; Hanum, Lathifah (Poltekkes Kemenkes Aceh, 2024)
Background: Abdominal surgery is a type of surgical operation performed on the abdominal area by making an incision in the lining of the abdominal wall to get parts of problematic organs such as bleeding, perforation, cancer, and obstruction. The incisions made during abdominal surgery cause large wounds and require a long recovery time and constant care, and are at risk of complications. The problem that often occurs in post-abdominal surgery patients is the lack of patient behavior to carry out early mobilization. Early mobilization is a series of light post-operative activities, starting from moving on the bed to being able to get out of bed, walk to the toilet, and get out of the toilet. Purpose: To determine the relationship between early mobilization and the wound healing process after abdominal surgery in the inflammatory phase. Methods: The quantitative research used a cross-sectional study method in the Surgical Ward of Meuraxa Hospital, Banda Aceh City from March 23 to May 20 2023. Data collected by interviewing and observe 30 postoperative patients who were selected according to the inclusion criteria and data analyzed by Chi-square test. Results: The results of the chi-square statistical test with CL=95% and α=0.05 showed a p-value of 0.032. This p value is <0.05, which means there is a significant relationship between early mobilization and the healing process of post-abdominal surgery wounds in the inflammatory phase. Conclusion: There is a relationship between early mobilization and the healing process of post-abdominal surgery wounds in the inflammatory phase.